Valorization of Eucalyptus nitens bark by organosolv pretreatment for the production of advanced biofuels - Romaní, Aloia (2019)
Supplementary data associated with this article can be found, in the online version, at: https://doi.org/10.1016/j.indcrop.2019.02.040.